2015
DOI: 10.1016/j.ejrad.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-thoracic rheumatoid arthritis: Imaging spectrum of typical findings and treatment related complications

Abstract: Non-cardiac thoracic manifestations of rheumatoid arthritis (RA) cause significant morbidity and mortality among RA patients. Essentially all anatomic compartments in the chest can be affected including the pleura, pulmonary parenchyma, airway, and vasculature. In addition, treatment-related complications and opportunistic infections are not uncommon. Accurate diagnosis of intra-thoracic disease in an RA patient can be difficult as the radiologic findings may be nonspecific and many of these conditions may coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 57 publications
0
20
0
14
Order By: Relevance
“…Chansakul TN, in their study, concluded that traction bronchiectasis and the extent of honeycombing (as our earlier findings illustrated in Figures 4-6) were strongly associated with morbidity and mortality [20]. RA related ILD carried a bad prognosis when they compared HRCT findings to pulmonary function tests.…”
Section: Figure 3: Axial Section Showing Bronchiectasismentioning
confidence: 60%
“…Chansakul TN, in their study, concluded that traction bronchiectasis and the extent of honeycombing (as our earlier findings illustrated in Figures 4-6) were strongly associated with morbidity and mortality [20]. RA related ILD carried a bad prognosis when they compared HRCT findings to pulmonary function tests.…”
Section: Figure 3: Axial Section Showing Bronchiectasismentioning
confidence: 60%
“…Los nódulos cavitados pueden complicarse originando abscesos, neumotórax y fistula broncopleural. 1,5 Pueden calcificarse y asociarse con neumoconiosis (síndrome de Caplan). 6 La TAC de tórax es la técnica radiológica más útil para identificar y definir las características de los nódulos, morfología, densidad, tamaño y permite seguir su evolución.…”
Section: Discussionunclassified
“…Su prevalencia varía según el estudio: por radiografía torácica 1% y por TAC de tórax 20-22%. 1 Aparecen tardíamente en el curso de la enfermedad. Su presentación clínica y radiológica puede confundirse con tuberculosis, infecciones fúngicas y cáncer pulmonar.…”
Section: Introductionunclassified
“…Rheumatoid arthritis (RA) is the most common form of chronic inflammatory arthritis; RA can cause noncardiac thoracic complications, such as pleuritis, emphysema, pneumothorax, interstitial pneumonia, and rheumatoid nodules [ 1 ]. Noncardiac thoracic complications of RA occur in 5–20% of RA patients and account for approximately 20% of RA-associated mortality [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%